2020
DOI: 10.1177/0253717620963202
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation in Psychiatry

Abstract: The COVID-19 pandemic has interrupted the usual mechanisms of healthcare delivery and exacerbated symptoms of mental illnesses. Telemedicine has morphed from niche service to essential platform, with newly released guidelines that cover various aspects of tele-mental health delivery. Rehabilitation services, which incorporate a range of psychosocial interventions and liaison services, have been significantly impacted too. They are currently more institute-based than community-based in India. However, recent le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 24 publications
1
34
0
11
Order By: Relevance
“…At the broader system level, several articles pointed to changes in regulation and reimbursements that have enabled clinicians practicing in a wide range of settings to quickly adopt e-mental health solutions for both existing and new patients struggling with the pandemic’s impact [ 29 - 31 , 52 , 67 ]. Patel et al identified a number of local and national collaborative approaches to care that have been developed since COVID-19, such as “Webinars for Nursing Homes” that have linked palliative care, geriatrics, and psychiatric old-age services in Ireland through Project ECHO AIIHPC (Extension for Community Healthcare Outcomes, All Ireland Institute of Hospice and Palliative Care) to help nursing home staff improve their knowledge of e-mental health tools [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the broader system level, several articles pointed to changes in regulation and reimbursements that have enabled clinicians practicing in a wide range of settings to quickly adopt e-mental health solutions for both existing and new patients struggling with the pandemic’s impact [ 29 - 31 , 52 , 67 ]. Patel et al identified a number of local and national collaborative approaches to care that have been developed since COVID-19, such as “Webinars for Nursing Homes” that have linked palliative care, geriatrics, and psychiatric old-age services in Ireland through Project ECHO AIIHPC (Extension for Community Healthcare Outcomes, All Ireland Institute of Hospice and Palliative Care) to help nursing home staff improve their knowledge of e-mental health tools [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various countries have also introduced new legal and practice guidelines to assure patient privacy and quality of care [ 26 , 27 ]. In India, the Medical Council released the Telemedicine practice guidelines in May 2020 to help remove some of the administrative and legal concerns present in practicing virtual care [ 27 - 29 ]. The COVID‑19 pandemic has also pushed some governments to make online or digital mental health resources widely available to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…When we delivered interventions through telephone, there were no national guidelines about telepsychotherapy, but our telephone-based session delivery and documentation match the latest guidelines for Tele-psychotherapy services [2,7]. Telephonebased intervention is a step to enhance the reach of psychosocial intervention to more people in the community who otherwise might struggle to engage in these services as the pandemic has shown the need for modifying the healthcare delivery system and the importance of telerehabilitation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Type of article 30 (49) Experience feedback [5,7,[42][43][44][45][46][47][48][49][50][51][52][53] 14 (23) Literature review [54][55][56][57][58][59][60][61][62] 9 (15) Study [63][64][65][66][67][68][69][70] 8 (13) Reflection Location of study [5,13,14,18,19,26,27,29,31,33,36,38,40,42,44,50,54,…”
Section: References Studies (N=61) N (%) Characteristicsmentioning
confidence: 99%